Determinants of willingness to adopt farm service centres among farming households in Abia State, Nigeria - Olurinde Kingsley Olusola; Agboola Luqman Wole; Oladunni Olufemi Ajayi (Agricultura Tropica et Subtropica)
The uptake of new agricultural technologies/innovations is not devoid of some challenges in Nigeria. However, to increase the production level in the sector, there is a need to enhance the adoption of new technologies/innovations. Therefore, this study examined the determinants of willingness to adopt farm service centres among farming households in Abia State, Nigeria. The study collected primary data from 300 farming households with a questionnaire using a three‑stage sampling procedure. The collected data were analysed using descriptive statistics and a binary logistic regression model. Results of socioeconomic characteristics revealed that farming activities in the area were male (58.7 %) dominated, mostly married (82 %) with a mean age of 50 ± 9.7, having 10.5 ± 5.8 mean years of formal education, operating on 0.87 ± 1.3 hectare of farmland with 21 years of farming experience. Binary logistic model result revealed that age, level of education, and farming experience were the factors determining the willingness to adopt farm service centres in the area. The need to boost farmers’ knowledge through an adult literacy programme, and involvement of relatively old farmers in empowerment programme as well as encouraging farmers’ participation in farmers’ associations in the study area is hereby recommended.